Analisis Persepsi Konsumen Prabayar/Token Listrik pada Kualitas Pelayanan terhadap Kepuasan Konsumen pada PT PLN (Persero) Unit Area Tanjung Selor Kabupaten Bulungan - Muh. Riza Permadi (Universitas Batanghari, 2022)
The purpose of this study is to determine whether the service variables consisting of reliability, responsiveness, assurance, empathy, and tangible simultaneously have a significant influence on customer satisfaction Prepaid at PT. PLN (Persero) Tanjung Selor Area. And to find out which of the service variables consisting of reliability, responsiveness, assurance, empathy, and tangible partially have a dominant influence on customer satisfaction Prepaid at PT. PLN (Persero) Tanjung Selor Area. The analytical model used in this study is in the form of Multiple Linear Regression (Multiple Linear Regression). The first hypothesis which states that it is suspected that the service variables consisting of reliability, responsiveness, assurance, empathy, and tangible simultaneously have a significant influence on prepaid customer satisfaction at PT. PLN (Persero) Tanjung Selor Area. Accepted, this is evidenced by the value of F arithmetic > F table. The second hypothesis which states that tangible partially has a dominant influence on consumer satisfaction at PT. PLN (Persero) Tanjung Selor area is accepted, this is evidenced by the tangible variable (X5) which has a t count greater than other variables.